PENANAMAN OBAT KELUARGA (TOGA) DALAM MENDUKUNG PENCEGAHAN COVID-19 DI DESA CIMANDIRI KABUPATEN LEBAK - Utami, Wahyu Kartiko; Akbar, Bagus Istigosah (Universitas Sultan Ageng Tirtayasa, 2021)
ThiscommunityserviceactivitywascarriedoutinCimandiriVillage,PanggaranganDistrict, LebakRegencywith theaimofincreasing communityknowledgeand technologyin aneffort topreventCOVID-19throughincreasing communityimmunity.Effortstopreventorincrease communityimmunityarecarriedoutbyplanting variousfamilymedicinalplantsinthe community'syard.Communityserviceiscarriedoutasoneofthevillageprogramstoincreaseimmunityorfamilyhealththroughplantingfamilymedicineinthecommunity's yard.In additiontoeffortstopreventCOVID-19throughincreasingcommunityimmunity,theplanting offamilymedicinalplantsisalsooneoftheusesofthecommunity'shomepagein Cimandiri Village,mostofwhichhavenotbeenutilizedproperlybythecommunity.Optimizingtheuseof thecommunity'shomeyardwithvariousfamilymedicinalplantsisalsoexpectedto increase thefamily'seconomybecausethesemedicinalplantscanlaterbeusedbythe communityfor theirdailyneedstotheneedtoimprovepublichealth.Cimandirivillageitselfisanareawhere mostofthepopulationworksasfarmerswithagriculturallandareasthatdominatethevillage. Sotheplantingoffamilymedicinalplantsisanalternativesolution forthecommunityin utilizing thehomepagewhileincreasing immunitythroughfamilymedicinalplantsorlive pharmacies.Familymedicinalplantsareanalternativetochemicaldrugs,especiallyplanting familymedicineismuchcheaperandpracticalthatcanbedonebyvariouscommunitygroups consideringthatmultivitaminsormedicinesforimmunityarenotcheap. Afterconducting socializationabouttheimportanceoffamilymedicinalplants,empowerment activities continuedwith theprovisionoffamilymedicinalplantseedsandplanting offamilymedicinal plant seedsin several placesinthe Cimandiri villagecommunityyard. Planting family medicineisalsoonewaytotakeadvantageofvacantlandwhichissometimesnotusedproperly bythecommunity